SECOND YEAR MBBS STUDENTS' VIEWS ABOUT FLIPPED CLASS ROOM PRACTICE IN NEUROANATOMY COURSE - Memon, Samreen; Goswami, Pushpa; Iqbal, Aamir Iqbal; Baloch, Saira (Journal of Postgraduate Medical Institute, 2016)
Objective: To assess students' insights about flipped classroom approach for neuroanatomy course and evaluate the effect on their performance in the end unit test. Methodology: This study was conducted at the Department of Anatomy, Liaquat University of Medical & Health Sciences for the academic session 2014. Neuroanatomy was chosen to evaluate the flipped classroom model for second year medical students. Three hundred and forty fourth semester medical students attended course. Students were divided into six groups and course contents were delivered into traditional lectures followed by flipping the small group classes. In lectures teacher delivered the topics with the help of multimedia and in flipped class students were encouraged to participate actively. They were provided case scenarios and teaching material before scheduled class. Students' perceptions were assessed by asking them to fill questionnaires. The post unit test was conducted to evaluate the effectiveness of this method. Results: Ninety-six percent of students believed that the flipped classroom approach was better in targeting learning objectives than the conventional teaching, 95% thought that the work-sheet with questions provided before class enabled a better understanding of the subject and 85% were of the opinion that the flip class approach was useful to understand the anatomical basis of neurological problems. The unpaired t test showed highly significant differences between the post unit test scores of this batch in comparison to previous batch who were only taught neuroanatomy with traditional teaching modes. Conclusion: Student response to the flipped classroom structure was very positive, signifying the importance of this approach as attractive method to pursue in future years for medical studies.